2017
DOI: 10.1016/j.jaubas.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Money laundering regulatory risk evaluation using Bitmap Index-based Decision Tree

Abstract: This paper proposes to evaluate the adaptability risk in money laundering using Bitmap Index-based Decision Tree (BIDT) technique. Initially, the Bitmap Index-based Decision Tree learning is used to induce the knowledge tree which helps to determine a company's money laundering risk and improve scalability. A bitmap index in BIDT is used to effectively access large banking databases. In a BIDT bitmap index, account in a table is numbered in sequence with each key value, account number and a bitmap (array of by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…For instance, a DM model is presented in [6] that applied K-means clustering and Association Rule Mining for identifying suspected sequence of money laundering processes. A novel technique named Bitmap Index-based DT was proposed in [32] for evaluating the risk factor of money laundering with Statlog German credit data.…”
Section: Security and Fraud Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a DM model is presented in [6] that applied K-means clustering and Association Rule Mining for identifying suspected sequence of money laundering processes. A novel technique named Bitmap Index-based DT was proposed in [32] for evaluating the risk factor of money laundering with Statlog German credit data.…”
Section: Security and Fraud Detectionmentioning
confidence: 99%
“…Security and fraud detection [6, classification (DT, NN, SVM, NB), k-mean clustering, ARM Australia [12], Latin-America [29], Greece [24], Germany [32], Belgium [21], UCI Repository [15][16][17][18] Identifying phishing, fraud, money laundering, credit card fraud, security trend of mobile/online/traditional banking.…”
Section: References Key Techniques Regions Purposesmentioning
confidence: 99%
“…Radial basis function neural network has been used in [20]. On the other hand, the decision tree approach has been applied in [21]- [24]. In another recent work [25], an adaptive neuro-fuzzy inference system is adopted for the AML problem.…”
Section: State Of the Art A Data Science Approachesmentioning
confidence: 99%
“…Among supervised learning works in the AML domain, [19], [20] have adopted transaction features such as sum and frequency of monetary transactions and [21], [24] have developed models with CRM features. However, there is no example combining these two characteristics.…”
Section: State Of the Art A Data Science Approachesmentioning
confidence: 99%
“…Bitmap Index-based DT (BIDT) algorithm was implemented by Jayasree and Balan [13] to evaluate the adaptability risk for money laundering. Results of false positive and true positive rates, alongside the adaptability rate and risk identification time, showed that the proposed approach outperformed other methods.…”
Section: Related Workmentioning
confidence: 99%